Comparison of manual lymphatic drainage massage and negative pressure massage therapy efficacy in lymphedema patients: a randomized controlled study - Ersoy, Sedef; Kesiktaş, Nur; Şirin, Büşra; Buğdaycı, Nazlı Derya; Kibar, Halime; Paker, Nurdan (The European Research Journal, 2023)
Objectives: Lower extremity lymphedema due to secondary causes is a lifelong complication that can be encountered. Its treatment is essential, because it has significant impact on quality of life and daily living activities related to lower extremity involvement. This research aims to compare the effects of Manual Lymphatic Drainage Massage (MLD) and Negative Pressure Massage Therapy (NPMT) treatments in order to provide maximum benefit to patients. Methods: This prospective, randomized study included 30 patients with lower extremity lymphedema due to secondary causes. Patients, randomized using computer software, were divided into two groups. The first group (n =15) received 45 minutes, 15 sessions of MLD, while the second group (n =15) received 45 minutes of 15 sessions of NPMT using the LymphaTouch device. Compression bandaging was applied to both groups and self-drainage training was given to all patients. The circumference of the extremity at 6 reference points were measured and their pain and discomfort assessed by the Visual Analogue Scale (VAS) were recorded before and after treatment. Changes within the groups and between the groups were compared using the SPSS statistical program. Results: Statistically significant improvement was observed in all parameters in both treatment groups. The decrease in VAS pain and VAS discomfort scores (p < 0.05 and p < 0.01; respectively), circumference measurement of the extremity (p < 0.01) was statistically greater in the NPMT group compared to the MLD group. Conclusions: In conclusion, NPMT appears to be a beneficial non-invasive treatment method for reducing extremity volumes and decreasing subjective pain and discomfort in lymphedema patients.